2021
DOI: 10.1002/cb.1963
|View full text |Cite
|
Sign up to set email alerts
|

Food waste in Australian households: Role of shopping habits and personal motivations

Abstract: The intensity of household food waste is of concern throughout the world, especially, in developed countries like Australia where it accounts for 34% of all food wasted along the value chain. Due to these concerns, there has been an emergence of research over the last decade to support policy interventions. This study contributes to this body of knowledge by examining the influence of consumer shopping habits and motivational factors on the intensity of food wasted by Australian households. Based on data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…Consumers may form positive attitudes toward food waste reduction, believing that it saves money or time. Many studies have confirmed this premise, showing that positive attitudes (e.g., saving money) encourage food waste reduction (Graham‐Rowe et al, 2015; Nabi et al, 2021; Visschers et al, 2016). Other studies have found a non‐significant association between attitudes and intentions (Russell et al, 2017).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 93%
“…Consumers may form positive attitudes toward food waste reduction, believing that it saves money or time. Many studies have confirmed this premise, showing that positive attitudes (e.g., saving money) encourage food waste reduction (Graham‐Rowe et al, 2015; Nabi et al, 2021; Visschers et al, 2016). Other studies have found a non‐significant association between attitudes and intentions (Russell et al, 2017).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 93%
“…Recent research has used audience segmenting to identify specific community engagement strategies [24][25][26]97,98]. This runs alongside studies into use of social media marketing and messaging, with the latter showing better results in raising household food waste awareness than the more traditional methods [23,33,99].…”
Section: Engagement and Empowerment: Generating Pro-environmental Pat...mentioning
confidence: 99%
“…These toolkits apply branches of current research to support and advise individual councils. These branches range from behaviour change [23][24][25][26] and community engagement methodologies [27][28][29], to analysis of governance [3,30], and system research and review [31][32][33]. With system selection at the discretion of the councils, these toolkits aim to provide adaptable situational analysis tools, methods, and implementation choices, with a strong emphasis on supporting pro-social/environmental behaviours [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Romani et al ( 2018) stated that, food preparation skills have a huge influence on potential food waste produced through leftovers. Food management skills that livelihood in reducing food subsequently being wasted such as need to know the right portion sizes to cook, think about on how to recycle leftover ingredients and leftover components of prepared meals, also the precise serving amount which will be eaten onto plates (Nabi et al, 2021;Van Dooren, 2019;Van Dooren et al, 2020). There are some potential reasons why by cooking at home leads to lower food waste is because through cooking at home, it can evolve cooking skills, be more efficient cook, know how to use of leftover, have a better estimation of how much food to cook and raise the awareness regarding of expiration dates of food stocks (Kubíčková et al, 2021;Pires et al, 2021).…”
Section: Understanding Family Preferences and Leftovers Managementmentioning
confidence: 99%
“…There are some potential reasons why by cooking at home leads to lower food waste is because through cooking at home, it can evolve cooking skills, be more efficient cook, know how to use of leftover, have a better estimation of how much food to cook and raise the awareness regarding of expiration dates of food stocks (Kubíčková et al, 2021;Pires et al, 2021). Aside from cooking skills, other skills which is related to dispose of leftover food such as the aptitude to use the senses to distinguish whether foods are safe to eat or not, and do not have any knowledge regarding of food date labels such as the 'best before' and 'use by' system operating in many countries including Australia (Nabi et al, 2021;van Dooren, 2019;van Geffen et al, 2020). Based on study by Pires et al (2021), discovered that by using leftover foods was the most significant reason of food waste lessening and 25% of the respondents recycled leftover foods during the pandemic by developing creative recipes.…”
Section: Understanding Family Preferences and Leftovers Managementmentioning
confidence: 99%